Electronic information trasmission for salary crediting (a case study of Singapore banks). - Yap, Alvin Kok Wai. (2008)
The introduction of faster and more reliable network in the Internet environment has promoted the use of Electronic Data Interchange (EDI) for many applications in many industries, in particular, the financial and banking industry.